2005
DOI: 10.1103/physrevlett.95.177602
|View full text |Cite
|
Sign up to set email alerts
|

Field Emission Patterns from First-Principles Electronic Structures: Application to Pristine and Cesium-Doped Carbon Nanotubes

Abstract: A general approach is introduced to calculate field emission properties of any kind of nanostructure based on the first-principles local density of states (LDOS) and effective potentials. The experimental field emission spectroscopy images are explained as LDOS at the structure-vacuum barrier, weighted by the probability of electron tunneling. The method excellently reproduces the experimental field emission patterns of pristine capped carbon nanotubes. We show that cesium adsorbates even with a low doping rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 30 publications
2
42
0
Order By: Relevance
“…Khazaei et al introduced a general approach to calculate the field emission properties of nanostructures. Pristine capped carbon nanotubes were studied, and the results agree well with experiments [69]. Furthermore, the authors demonstrated that the structures can be modified to have better field emission properties through doping Cs atoms to nanotubes [69].…”
Section: Design Of Novel Devicesmentioning
confidence: 79%
“…Khazaei et al introduced a general approach to calculate the field emission properties of nanostructures. Pristine capped carbon nanotubes were studied, and the results agree well with experiments [69]. Furthermore, the authors demonstrated that the structures can be modified to have better field emission properties through doping Cs atoms to nanotubes [69].…”
Section: Design Of Novel Devicesmentioning
confidence: 79%
“…The diamond and graphite had film thicknesses of 1.075 nm and 1.579 nm, respectively. 8,14 Equation (1) is the Khazaei's equation. 2.…”
Section: Ab Initio Dft Calculationmentioning
confidence: 99%
“…In order to further understand the field emission properties of B-doped CNTs, the tunneling probabilities have been calculated using the method presented by Khazaei et al [41]. Fig.…”
Section: Tunneling Probabilitymentioning
confidence: 99%